Genomics and Biodiversity: Applications and Ethical Considerations for Climate-Just Conservation - Miner, Skye A. (The Hastings Center report, 2024)
Genomics holds significant potential for conservationists, offering tools to monitor species risks, enhance conservation strategies, envision biodiverse futures, and advance climate justice. However, integrating genomics into conservation requires careful consideration of its impacts on biodiversity, the diversity of scientific researchers, and governance strategies for data usage. These factors must be balanced with the varied interests of affected communities and environmental concerns. We argue that conservationists should engage with diverse communities, particularly those historically marginalized and most vulnerable to climate change. This inclusive approach can ensure that genomic technologies are applied ethically and effectively, aligning conservation efforts with broader social and environmental justice goals. Engaging diverse stakeholders will help guide responsible genomic integration, fostering equitable and sustainable conservation outcomes.